Sistem Kendali Jarak Jauh dan Monitoring Penggunaan Listrik pada Pompa Air melalui Smartphone: Studi Kasus: Kos XYZ Kota Padang - Fauzi, Ahmad; Aisuwarya, Ratna (JITCE (Journal of Information Technology and Computer Engineering), 2020)
This study aims to create a control system that can turn on / turn off the water pump by simply pressing a button on the smartphone and monitoring how much electricity was used which will later be converted into cost value in rupiahs. This system is able to further regulate the use of water pumps, such as restrictions on daily use, restrictions on use at certain hours, and pumps can be set to automatically shut down after a few moments of use. This system consists of three main components, namely an embedded system, a website-based mobile application, and a web server. The embedded system consists of Wemos D1, ACS712 current sensor, and relay. From the tests conducted the system can turn on the water pump with an average response time of 2 seconds and the results of monitoring conducted have an average error value of 13.63%.